1047 VALIDATION OF THE CHINESE VERSION OF THE KATZ INDEX OF INDEPENDENCE IN ACTIVITIES OF DAILY LIVING. (14th June 2022) - Chui, D L K; Yeung, C K; Choi, C W; Leung, M N; Lui, Y; Tam, W Y; Tang, K Y; Wong, C; Wong, Y; Yau, C Y; Yeung, T L; Lee, J K L; et al.
Abstract: Introduction: Among the instruments that measure an elder's functional dependence level, the Katz Index of Independence in Activities of Daily Living has the advantages of being neutral, easy to use, valid, and reliable. It is a six-item instrument rating an elder's functional dependence level in performing activities of daily living, including bathing, dressing, toileting, transferring, continence, and feeding. Each item can be rated nominally as 1 (does not require assistance to finish the activity) or 0 (requires assistance to finish the activity). By summing the score of the six items, the functional dependence level of an elder can be classified as independent (6 points), partially dependent (3–5 points), or dependent (< 2 points). The instrument has been translated from English to Chinese through forward and backward translation. This study aims to validate the Chinese version of the Katz Index of Independence in Activities of Daily Living (Katz ADL-Chinese). Method: This was a validation study. The Katz ADL-Chinese was examined by an expert panel (one academic specialized on instrument validation, four academic specialized on translation, fifteen nurses specialized on geriatrics) for its semantic and content equivalence with the original English version. It was evaluated by another expert panel (one academic specialized on instrument validation and two nurses specialized on geriatrics) for its content validity. Moreover, it was tested and re-tested at 1-week interval on 30 Chinese-speaking elders in Hong Kong. Results: Good result was achieved on the testing for semantic and content equivalence. All experts confirmed that the Katz ADL-Chinese was appropriately translated. Good content validity was observed. The context validity index at item-level and scale-level was 1.00, respectively. Good stability was observed as well. The test–retest reliability coefficient was 0.85.